Respuestas

  • Usuario de Brainly
2014-01-13T01:38:44+01:00
Solución:
a) A + B + C = (-5 + 3i) + ( 8 - 7i) + (-5 + 9i)= (-5+8-5) + (3i - 7i + 9i) = -2 + 5i ..Rta.

b) A - B - C = (-5 + 3i) - ( 8 - 7i) - ( -5 + 9i) = (-5 - 8 + 5) - ( 3i - 7i + 9i) 
.............................................................= -8 - (5i)
.............................................................= -8 - 5i .....Respuesta.

c) A*B*C = (-5 + 3i)(8 -7i) ( -5 +9i) = (-40 + 59i -21i^2) ( -5+ 9i)
..................................................= (-19 + 59i) ( -5 + 9i)
..................................................= 95 - 466i + 53i^2
..................................................= 95 - 466i - 53
..................................................= 42 - 466i......Respuesta.

d) B / C = 8-7i / (-5 + 9i ) = (8-7i)(5 - 9i) / (-5 + 9i)(5 - 9i)
.....................................= (40 - 107i + 63i^2) / ( -25 + 90i - 81i^2)
.....................................= (40 - 107i - 63) / ( -25 + 90i + 81)
.....................................= ( -23 - 107i ) / (56 + 90i) ,,,,,,,,Respuesta.
suerte. Kamillitha
te lo agradezco mucho
hipitia esas rayitas q significan :D